PROFIL BEBAN PADA SISTEM KELISTRIKAN UNIVERSITAS BANGKA BELITUNG - Wahri Sunanda (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2017)
University of Bangka Belitung is currently supplied by PLN Bangka Belitung region with 690 kVA power supply to meet the need of electric energy on campus with total land 153 ha. Through direct measurements on the panels of each building, it is found that the use of power in the morning is higher than the use of power in the afternoon. Total power (3 phases) in the morning ie 194.6425 kW, while in the afternoon 154,0396 kW.